English Teachers' Perceptions of a Language Assessment Literacy Course - Frank Giraldo; Daniela Escalante-Villa; Daniela Isaza-Palacio (Asociación Colombiana de Profesores de Ingles, 2023)
Language assessment literacy has gained recent attention in the field of language testing, particularly on teachers' profile. However, the literature on LAL is limited regarding teachers' perceptions of language assessment courses. In this paper, we used a case study method to characterize the perceptions of eighteen English language teachers into three components of an online assessment course: contents, activities, and impact on their professional development. For data collection, we used a questionnaire and a focus group interview. Findings indicate that the teachers perceived course contents as organized, relevant, and useful; they also considered test analysis and collaborative tasks as valuable. Regarding professional development, the teachers explained that test-analysis tasks made them aware of their mistakes in assessment. Finally, the teachers suggested that the course raised their awareness of what language assessment is and does. Based on these results, we provide recommendations for LAL courses elsewhere.